1985
DOI: 10.1128/iai.50.3.778-786.1985
|View full text |Cite
|
Sign up to set email alerts
|

Contact-dependent cytopathogenic mechanisms of Trichomonas vaginalis

Abstract: The cytopathogenic mechanisms of Trichomonas vaginalis have been debated since the 1940s. We examined the following three proposed pathogenic mechanisms: contact-dependent extracellular killing, cytophagocytosis, and extracellular cytotoxins. Serial observations of Chinese hamster ovary (CHO) cell monolayers exposed to trichomonads revealed that (i) trichomonads form clumps, (ii) the clumps adhere to cells in culture, and (iii) monolayer destruction occurs only in areas of contact with T. vaginalis. Kinetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(60 citation statements)
references
References 23 publications
7
53
0
Order By: Relevance
“…These factors, along with the possibility of functional exhaustion of phagocytes in a heavily contaminated bacterial environment, might also be responsible for the diminished functional capacity of live vaginal leukocytes. Trichomonads, though producing a cytopathogenic effect on various types of cells (1,16,17), did not reduce venous leukocyte viability and functional capacities in vitro (unpublished observation).…”
Section: Discussionmentioning
confidence: 89%
“…These factors, along with the possibility of functional exhaustion of phagocytes in a heavily contaminated bacterial environment, might also be responsible for the diminished functional capacity of live vaginal leukocytes. Trichomonads, though producing a cytopathogenic effect on various types of cells (1,16,17), did not reduce venous leukocyte viability and functional capacities in vitro (unpublished observation).…”
Section: Discussionmentioning
confidence: 89%
“…The absolute necessity of iron for growth and multiplication of T. vaginalis and the high iron requirement of this parasite (Gorretl, 1985) may make it impossible to overcome the nutritional immunity imposed by the host, if trichomonads relied only on the interaction of lactoferrin with its trichomonal receptor. The ability of trichomonads to lyse human erythrocytes (Krieger e( ai., 1983;Dailey e( al.. 1990) and HeLa celts and epithelial cells (Aiderete and Pearlman, 1984;Krieger et aL, 1985) has been established. That red blood cells and epithelial cell extracts stimulate growth in iron-limited medium ( Table 5) strongly suggests that intracellular iron sources, such as cytochromes, ferritin, and haemoglobin, are also likely iron sources for the parasite during infection.…”
Section: H L H H L H Discussionmentioning
confidence: 99%
“…The mechanism of cell damage utilized by T. vaginalis is not yet completely understood. It has been demonstrated that it is contact dependent [2], and the production of proteases that cause detachment of monolayer cells in vitro has been described [3].…”
Section: Introductionmentioning
confidence: 99%